Derogation of Human Rights During States of Emergency and the Standards of a Democratic Rule of Law - Krasuski, Andrzej (PRAWO i WIĘŹ, 2025)
This paper examines the legal ramifications of derogating from human rights during states of emergency in accordance with international law, with particular reference to the International Covenant on Civil and Political Rights. It is predicated on the hypothesis that the political system's nature may influence the extent of human rights restrictions. The discussion is structured around the following research inquiries: How are human rights defined under international law, and in what ways do democratic standards affect the process of derogation from human rights? The analysis evaluates the legal modifications enacted in Poland in response to the declaration of the COVID-19 pandemic. The study employs the formal-dogmatic methodology.